Adapting the Breast Cancer Surgery Decision Quality Instrument for Lower Socioeconomic Status: Improving Readability, Acceptability, and Relevance. Issue 2 (November 2018) - Durand, Marie-Anne; Song, Julia; Yen, Renata West; Sepucha, Karen; Politi, Mary C.; Dhage, Shubhada; Rosenkranz, Kari; Margenthaler, Julie; Tosteson, Anna N. A.; Crayton, Eloise; Jackson, Sherrill; Bradley, Ann; et al.
Introduction. Breast cancer is the second most common malignancy in women. The Decision Quality Instrument (DQI) measures the extent to which patients are informed and involved in breast surgery decisions and receive treatment that aligns with their preferences. There are limited data on the performance of the DQI in women of lower socioeconomic status (SES). Our aims were to 1) examine (and if necessary adapt) the readability, usability, and acceptability of the DQI and 2) explore whether it captures factors important to breast cancer surgery decisions among women of lower SES (relevance).Methods. We conducted semistructured cognitive interviews with women of lower SES (based on insurance status, income, and education) who had completed early-stage breast cancer treatments at three cancer centers. We used a two-step thematic analysis with dual independent coding. The study team (including Patient Partners and a Community Advisory Board) reviewed and refined suggested changes. The revised DQI was presented in two focus groups of breast cancer survivors.Results. We conducted 39 interviews. Participants found most parts of the DQI to be helpful and easy to understand. We made the following suggested changes: 1) added a glossary of key terms, 2) added two answer choices and an open text question in the goals and concerns subscale, 3) reworded the treatment intention question, and 4) revised the knowledge subscale instructions since several women disliked the wording and were unsure of what was expected.Discussion. The readability, usability, acceptability, and relevance of a measure that was primarily developed and validated in women of higher SES required adaptation for optimal use by women of lower SES. Further research will test these adaptations in lower SES populations.